Kedisiplinan Guru dalam Pembelajaran Sekolah Menengah Pertama di Pinggiran Kota Wamena, Kabupaten Jayawijaya : Studi Kasus SMP Negeri Walelagama - Yan Dirk Wabiser; Bernarda Meteray (FKIP, Universitas Palangka Raya, 2020)
The research in this journal aims to identify various factors that influence the lack of teacher discipline at SMP Negeri Walelagama. Based on a qualitative approach with a case study strategy. The results show that there are two vital factors affecting teacher discipline: internal and external factors. Internal factors include a lack of awareness of professional responsibilities and low teacher motivation. External factors include limited infrastructure, such as inadequate teacher housing, unfavorable security conditions, and minimal access to health services. Lack of assertiveness in rule enforcement also contributes to low teacher discipline. These findings suggest that improving discipline requires a holistic approach, including the provision of basic facilities and training programs that can increase teacher motivation. Thus, improving teacher discipline can lead to a more optimal learning environment.